Aquinas on the divine ideas as exemplar causes - Doolan, Gregory T. (Catholic University of America Press, 2008)
Gregory T. Doolan provides here the first detailed consideration of the divine ideas as causal principles. He examines Thomas Aquinas's philosophical doctrine of the divine ideas and convincingly argues that it is an essential element of his metaphysics.